CAKE FLOUR: FUNCTIONALITY AND QUALITY - Al-Dmoor, Hanee M. (European Scientific Journal, ESJ, 2013)
Many components are used in the production of cakes such as flour, water, sugar, milk, salt, leavening agent, flavors, additives and other food are allowed in the specifications. The quality and quantity of these components are important and influence on the properties of the final product as well as the stability of quality during shelf life. The most important factor in cakes making is the availability of soft wheat flour and the proportions of its components (8%) protein, gluten quality, strength and ash contents nearly (0.4 %). After mixing of cake flour and other ingredients form dough which accomplished to retain the leaved gas to reach the final soft structure of crumb and crust, volume, flavor and other quality parameters of cakes.